Exploring the Research Trends in Green Tax: Bibliometric Analysis - Babu, P. Ebin; Mary, Riya (International Journal of Energy Economics and Policy, 2022)
Policymakers, producers, and consumers all around the world have recognized the need for a sustainable model of development. However, there is a disconnect between the strategies put forth to achieve sustainability and the acceptance of sustainable development methods. The concept of "green tax" can speed up the adoption of ethical behaviors that support sustainability. A greater understanding of how different countries are implementing green taxes is necessary. By taking into account the papers published in Scopus journals in the English language, this study used the method of bibliometric analysis to comprehend the research done in the field of green taxes.